Gut microbiota and functional metabolic predictions in white feces disease-infected Pacific white shrimp, Penaeus vannamei, from Indonesian farms - Amin, Muhamad; Rahardjo, Karina Kristanti Ekarani; Panosa, Alief Erwaanda; Satyantini, Woro H.; Mukti, Akhmad Taufiq; Ali, Muhamad; Musdalifah, Laila; Akhyar, Halil; Yanuhar, Uun; Azmai, Mohammad Noor Amal; Arai, Takaomi (Academic Press, 2025)
The etiological agent of white feces disease (WFD) infecting Pacific white shrimp Penaeus vannamei in Indonesia farms remains obscure. The present study aimed to identify possible causative agents of WFD infection in Pacific white shrimps cultured in Indonesian farms. WFD-infected and healthy samples (shrimp gut and rearing water) were collected from 8 commercial shrimp farms in East Java, Indonesia followed by bacterial community profiling using HiSeq sequencing of 16S rRNA gene amplicons. The results showed that the microbiota composition in the guts of WFD-infected shrimps was significantly different (p < 0.05) from the guts of healthy shrimps in term of genus and bacterial species. The intestinal bacterial communities of WFS-infected shrimps were overrepresented by Vibrio coralliilyticus, whereas Paracoccus was underrepresented. Phylogenetic Investigation of Communities by Reconstruction of Unobserved States functional predictions indicated that relative abundances of 12 genes associated with the pathogenicity of bacteria including amino acid metabolisms, carbohydrate metabolisms, glycan biosynthesis, and xenobiotic biodegradation and metabolism were significantly (p < 0.05) higher in the gut microbiota of WFD-infected shrimps. These findings provide insights into the microbiome domination and their metabolic activities in the digestive tract of WFD-infected shrimps and suggest that V. coralliilyticus is a possible causative agent of WFD in cultured Indonesia Pacific white shrimp. © 2025 Elsevier Ltd